Libraries Driving Access to Knowledge in the Academic Environment - Ahenkorah-Marfo, Michael (Ghana Library Journal, 2012)
The paper seeks to take a technical view of access to knowledge resources and highlights the role of libraries in facilitating access to knowledge in the academic environment. It analyzes the processes involved in organization and retrieval of knowledge resources, which encompasses collection building, organization of knowledge through metadata extraction, and the use of retrieval systems to facilitate access to knowledge. The importance of, and the need for authority control in collocation, networking of the catalogue and facilitation of resource sharing locally and internationally are emphasized. The challenges associated with the use of controlled vocabulary as against free-text search in retrieval systems are not only highlighted but also addressed in order to improve efficiency of retrieval systems in general and precision in particular. The paper finally explores new ways of driving access to knowledge through social networking tools